Structure or Anarchy: A Bibliometric Analysis of Keywords in Cybersecurity Education Literature (Journal of The Colloquium for Information Systems Security Education, 2023)
Bibliometric analysis is essential for understanding the growth, health, and trajectory of scientific disciplines. In effect, such analyses help researchers determine if a given field is well-structured or fragmented through anarchy. Prior work examined to what extent cybersecurity education research generated a follow-up study. The goal of the work was to uncover bibliometric features and characteristics linked to overall maturity of the field. The results suggested little, if any, research follow up or extension took place based on the dearth of interlinking between citations. This work continues the line of bibliometric description by investigating if cybersecurity education papers are not extended because of discoverability issues during literature reviews. To answer this question, this work explored structural bibliometric indicators in 163 journal and conference articles. Specifically, we extracted metadata keywords and paper content keywords as input to frequency analyses of the sample articles. The results revealed 12.4% of the sample contains metadata keywords. Further, 18.03% of the sample contained educated related keywords. Lastly, four of the top five sample papers by citation count do not contain keywords at all and papers with content only keywords exhibited more frequent citation than those with only metadata keywords. Based on these results, we offer observational conclusions as well as notions for future work.
Keywords: Cybersecurity education; pedagogy; laboratories; bibliometrics